Content Analysis of Da'wah Messages in Revealing the Defense of Palestine on @Felixsiauw's YouTube Account - Lubis, Chaerona Artha; Kholil, Syukur (Manunggal Halim Jaya, 2024)
This study aims to reveal the content of da'wah messages in voicing the defense of Palestine which includes aqidah, sharia and ahlak contained in Ustadz Felix Siauw's da'wah material in his YouTube account with the title